Hard Inclusions in Armature Brass - Romankiewicz, Remigiusz; Romankiewicz, Ferdynand (Journal of Casting & Materials Engineering, 2019)
The influence of the chemical composition of selected armature brasses on the formation of hard inclusions was investigated. In metallographic studies using optical microscopy and scanning electron microscopy with X-ray microanalysis (EDS), it was found that hard inclusions attain sizes ranging from several hundred nanometers to several micrometers. Investigations of samples that were taken from metallurgical pigs of armature brass of various chemical compositions have shown that the contribution of components such as iron and silicon have a decisive influence on the formation of hard inclusions. These components have a dominant share in hard inclusions (60–76 wt.% Fe and 10.6–17.4 wt.% Si). In much smaller quantities there are also elements such as manganese, phosphorus, nickel and chromium. The chemical composition of hard inclusions varies. The number and size of hard inclusions depends on the contribution of iron and silicon brass. In the brass sample with 0.31 wt.% Fe and 0.08 wt.% Si, 1183 inclusions per square millimeters were identified, while in the brass sample with 0.21 wt.% Fe and 0.11 wt.% Si the amount of hard inclusions was reduced to 933 inclusions per square millimeters. In the brass sample with reduced iron content up to 0.08 wt.% and silicon up to 0.006 wt.%, no hard inclusions were identified.